2010
DOI: 10.1021/ja100944j
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of an ILPR i-Motif and a Partially Folded Structure with Comparable Mechanical Stability Revealed at the Single-Molecule Level

Abstract: Investigation of i-motif is of high importance to fully understand the biological functions of G quadruplexes in the context of double stranded DNA. Whereas single molecule approaches have profiled G quadruplexes from a perspective unavailable by bulk techniques, there is a lack of similar literature on the i-motif in the cytosine (C) rich region complementary to G quadruplex forming sequences. Here, we have used laser tweezers to investigate the structures formed in 5′-(TGTCCCCACACCCC)2, a predominate variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
137
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(152 citation statements)
references
References 61 publications
15
137
0
Order By: Relevance
“…The change in contour length (ΔL; see the Materials and Methods for the calculation) was determined to be 9.2 ± 0.1 nm, a value consistent with the contour length of the 27-mer ATP aptamer. 30,35 In a control with a scramble sequence (see the Materials and Methods) that does not assume any stable conformations, no folded structure was observed (data not shown), which strongly suggests that the observed events are due to the ruptures of folded ATP aptamers. The unfolding force at which the rupture event occurred showed a most probable value of 21 pN without the ATP ligand (Figure 2A).…”
Section: ■ Materials and Methodsmentioning
confidence: 96%
“…The change in contour length (ΔL; see the Materials and Methods for the calculation) was determined to be 9.2 ± 0.1 nm, a value consistent with the contour length of the 27-mer ATP aptamer. 30,35 In a control with a scramble sequence (see the Materials and Methods) that does not assume any stable conformations, no folded structure was observed (data not shown), which strongly suggests that the observed events are due to the ruptures of folded ATP aptamers. The unfolding force at which the rupture event occurred showed a most probable value of 21 pN without the ATP ligand (Figure 2A).…”
Section: ■ Materials and Methodsmentioning
confidence: 96%
“…GGGGGCTGGGCCGGAAACCCGGGAGGGGTCGGGACGGGGCGGGGC and 5′-GCCCCGCCCCGTCCCGACCCCTCCCGGGTTTCCGGCCCAGCCCCC; mutated bases are underlined) between two double-stranded DNA handles, according to published procedures. 54 Five deoxythymidines were added at both ends of the hTERT 5-12 fragment to reduce the interference from the double-stranded DNA handles on the target sequence. Briefly, the 2690-base-pair double-stranded DNA handle was prepared through restriction enzyme digestion of the pEGFP vector (Clontech, Mountain View, CA).…”
Section: Methodsmentioning
confidence: 99%
“…where x is the end-to-end distance for G-quadruplex or i-motif structures (0.5-1.5 nm) 54 and subjected to dual-luciferase assay (Promega) using an FB12 luminometer. The ratio of firefly to renilla luciferase activity was normalized to the DMSO to obtain the relative luciferase activity.…”
Section: Methodsmentioning
confidence: 99%
“…The specific binding of i-motif-forming sequences to various proteins implies the potential biological function of i-motifs that may form in these sequences. More recently, Mao and co-workers have indicated that i-motif structure may interfere with RNA transcription [21]. But until now a few of small molecules that interact with i-motif DNA have been reported [22,23].…”
Section: Introductionmentioning
confidence: 99%